ISOLASI, IDENTIFIKASI DAN UJI TOKSISITAS SENYAWA FLAVONOID FRAKSI KLOROFORM DARI DAUN TERAP (ARTOCARPUS ODORATISSIMUS BLANCO) - Nur Tasmin; Erwin -; Irawan W Kusuma (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2014)
The research about the characterization of flavonoid compound from the leaves of plants applicability chloroform(artocarpus odoratissimus Blanco). Extraction plants done by maceration method and separation of compounds wasperformed using the technique of vakum liquid chromatography and chromatography colomn flash. Separation resultobtained yellowish-white powder. Resul spectrum UV-visible absorption obtained namely the 254.37 to 181.28 areaabsorbance wavelength (nm), while FT-IR analysis result provide absorption at wavenumber there is an alkyl group, ahydroxyl group, an aromatic group and C-O-C stretching based on the data spectrum UV an IR spektrun can beconcluded that the compounds suspected isolated belonged to the Flanva-3-ol. Toxicity was conducted for prawn larvaeArtemia salina Leach. Effect of toxicity from isolate identified with presentage of prawn larva and counted by probitanalysis (LC 50 ). The results of this test showed that the the isolate was very toxic with LC 50 value of 26,8824 ppm. Thetest result obtained mortality of shrimp larvae LC 50 value of each sample is 110.5176 ppm total extract, chloroformfraction 147.7895 ppm, and isolate 80.2568 ppm.Keywords : Terap (Artocarpus odoratissimus Blanco), Isolation, Flavonoid, BSLT